Characterization Of Charcoal Product Of Pyrolisis Of Human Hair Waste Activated With KOH Solution - Kojongian, Tammita Marianne Kireina; Krisen, Sofia; Anom, I Dewe Ketut (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
This research aims to characterize charcoal resulting from pyrolysis of human hair waste which is activated by KOH solutions using FTIR, XRD and SEM instruments. The human hair charcoal obtained from pyrolysis then goes into the particle size reduction process using a 60 and 100 mesh sieve. It is then activated using KOH and then the results of the activation are analyzed using FTIR, XRD instruments assisted by software. Origin and Ms. Excel, then SEM assisted by Image-J software . The ash content test results show that the amount of minerals and metals in human hair charcoal tends to increase. The results of the water content test show that the amount of water content in human hair charcoal tends to decrease. In analysis using FTIR it was identified showed the presence of various functional groups in human hair charcoal processed with KOH and Control Sample solutions. Mesh differences in processing give slight variations in peak intensity and position, but overall indicate the presence of O-H, CH, C=C, and CO groups . In the analysis using​ The solution gave the largest grain size in KOH mess 100, namely D = 356.35764 ± 11.18168 nm.